Opening new horizons seeds of a theology of religious pluralism in Thomas Merton's dialogue with D. T. Suzuki - Raab, Joseph Quinn (Pickwick Publications, 2021)
"On the surface Christianity and Zen Buddhism can appear to be worlds apart, even antithetical. Christianity affirms the reality of the Tri-personal God and the eternal salvation of mortal human beings; Zen denies both the existence of God and the soul. Yet Thomas Merton, the Catholic spiritual master, and D. T. Suzuki, the famous teacher of Zen, engaged in an extensive dialogue and found ways of mutually affirming shared meanings of God and person that each regarded to be true. This book explores that dialogue within the larger context of Merton's attraction to Buddhism and considers the implications of their achievement for contemporary theologies of religious pluralism."--Cover
Keywords: Merton, Thomas -- 1915-1968; Suzuki, Daisetz Teitaro -- 1870-1966; Religionstheologie; Religiöser Pluralismus; Merton, Thomas / 1915-1968; Suzuki, Daisetz Teitaro / 1870-1966; Trappists / United States; Zen Buddhists; Trappists; United States